Kajian Penerapan Pemeriksaan Persyaratan Teknis Pada Unit Pelaksana Uji Berkala Kendaraan Bermotor Sesuai Buku Pedoman Pengujian Kendaraan Bermotor Jilid II B Dan II D - Novianto, Arief; Eska Fahmadi, Aat; El Tosi, Vinno (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2022)
Motor vehicle testing is a series of activities to test and/or inspect parts of motorized vehicles, trailers, patch trains and special vehicles in the context of meeting technical requirements and roadworthiness both visually and manually. The problem faced is that there is no uniformity of technical services carried out in each of the Implementing Units of the Periodic Motorized Vehicle Test (UPUBKB). The purpose of this study was to determine the suitability of items and the flow of the technical inspection process in UPUBKB with those in the motor vehicle testing manual volumes II B and II D. The sampling method used in this study was simple random sampling, amounting to 32 UPUBKB. from a total population of 212 UPUBKB in Indonesia that have obtained accreditation A and B. The data collection method used is literature study and observation using a questionnaire (Likert scale) and a check list. The submission of questionnaires and checklists was carried out offline and online to 32 UPUBKB locations spread throughout Indonesia. The data will be analyzed descriptively quantitatively. The results of the study showed that only 53% or 17 UPUBKB had the flow of the vehicle technical inspection implementation process in accordance with the motor vehicle testing manual, 47% of the UPUBKB samples did not comply with the technical inspection flow. Of the 17 UPUBKB, there are 7 UPUBKB accredited A and 10 UPUBKB accredited B. Meanwhile, of the 32 samples of UPUBKB, not all of them have carried out technical inspections in accordance with the items in the motor vehicle testing manual, and based on the questionnaire, the examiner respondents at UPUBKB strongly agree (92 .5%) and expects a national standard for technical inspection of motor vehicles.